Assessing Effects of Eye Position on Vestibular Evoked Myogenic Potential - Sahar Shomeil Shushtary; Nader Saki; Soheila Nikakhlagh; Mojtaba Tavakoli; Meymaneh Jafari (Vesnu Publications, 2015)
Introduction: Vestibular evoked myogenic potential is useful test for assessing function of saccule and inferior vestibular nerve. Vestibular evoked myogenic potential Amplitude is proportional to the level of background Electomyography. In the post-auricular muscle, magnitude of the Electomyography is directly related to the position of the eye. Therefore, this study aimed to assess if eye position effect on Vestibular evoked myogenic potential. Materials and Methods: In this cross-sectional study, vestibular evoked myogenic potential was recorded for 30 normal subjects, aged 18 to 30 years old, using 500 Hz-tone bursts (95 dBnHL) in three eye position: (1) eyes in the same direction as head turn, (2) eyes straight ahead, (3) eyes in the opposite direction to head turn in both ears. Results: In both ears, there was significant difference between mean amplitude of all three positions (P < 0.05). In both ears, mean amplitude of Vestibular evoked myogenic potential in eyes in the opposite direction to head turn was smaller and in eyes in the same direction to head turn was larger than the other two positions. In all three positions and in both ears, mean p13 and n23 latencies did not show any significant difference (P > 0.05). Conclusion: Results of this study shows that magnitude of the response alters depending on the position of a subject's eyes during recording vestibular evoked myogenic potential. So controlling eye position during recording test is recommend.